2019
DOI: 10.1101/753244
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pharmacological or genetic targeting of Transient Receptor Potential (TRP) channels can disrupt the planarian escape response

Abstract: 25In response to noxious stimuli, planarians cease their typical ciliary gliding and exhibit 26 an oscillatory type of locomotion called scrunching. We have previously characterized the 27 biomechanics of scrunching and shown that it is induced by specific stimuli, such as 28 amputation, noxious heat, and extreme pH. Because these specific inducers are known to 29 activate Transient Receptor Potential (TRP) channels in other systems, we hypothesized that 30 TRP channels control scrunching. We found that … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…As mentioned, TRPV channel activation has been observed in response to anandamide in mammalian models [123,124]. A recent study demonstrated that two previously identified TRPV-encoding genes (DjTRPVa and DjTRPVb) partially mediate anandamide sensing in Dugesia japonica [122]. Exposure to 100 μM of anandamide resulted in the scrunching behaviour associated with noxious stimuli, as well as an unexpected increase in head lifting or head wiggling [122].…”
Section: Platyhelminthesmentioning
confidence: 89%
See 3 more Smart Citations
“…As mentioned, TRPV channel activation has been observed in response to anandamide in mammalian models [123,124]. A recent study demonstrated that two previously identified TRPV-encoding genes (DjTRPVa and DjTRPVb) partially mediate anandamide sensing in Dugesia japonica [122]. Exposure to 100 μM of anandamide resulted in the scrunching behaviour associated with noxious stimuli, as well as an unexpected increase in head lifting or head wiggling [122].…”
Section: Platyhelminthesmentioning
confidence: 89%
“…Planarians display what is known as "scrunching" in response to noxious stimuli, such as low pH, elevated temperatures, or amputation [121,122]. This behaviour is described as a ciliaindependent alteration in oscillatory gait, which is thought to be mediated through the TRP channels [121,122]. As mentioned, TRPV channel activation has been observed in response to anandamide in mammalian models [123,124].…”
Section: Platyhelminthesmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, because different researchers used different planarian species, varying experimental conditions and manual scoring metrics, which were rarely described in detail and may have suffered from experimenter bias (reviewed by (Jenkins, 1967) and summarized in Table S1), it is difficult to compile and interpret these previous findings. Therefore, we decided to revisit planarian electrotaxis with modern experimental tools and a quantitative and automated approach using the species Dugesia japonica, a popular species for planarian behavioral studies (Shomrat and Levin, 2013;Inoue, Yamashita and Agata, 2014;Inoue et al, 2015;Sabry et al, 2019;Zhang et al, 2019;Ireland et al, 2020;Le et al, 2021).…”
Section: Introductionmentioning
confidence: 99%